Development and Application of the Paced Bottle-Feeding Checklist - Taylor N. Richardson; Melissa C. Kay; Alison K. Ventura (Journal of Nutrition Education and Behavior, 2026)

A comparison of hydrological impacts from two ensembles of regional climate projections with a range of climate sensitivities - Alison Lindsey Kay (Regional Environmental Change, 2025)
Understanding the range of potential impacts of climate change is crucial for appropriate adaptation planning, especially for floods and water resources. Driving hydrological models with data from climate models provides important information, but can be limited by availability and useability of appropriate climate ensembles for the region of interest. Here, a recently re-processed multi-model ensemble of regional climate projections, derived from Euro-CORDEX, has been used alongside a regional perturbed parameter ensemble, from UK Climate Projections 2018, to drive a national-scale grid-based hydrological model, to assess future impacts on river flows across Great Britain. The results show relatively consistent increases in GB-median winter flows and 5-year return period high flows, but the magnitude of GB-median decreases in summer flows is more different between the two ensembles, as are reductions in 5-year return period low flows. The signs of GB-median changes in spring and autumn flows are inconsistent. Spatial patterns of change also show significant differences between ensemble members. Assuming the climate model results are all plausible, adaptation planning for Britain should take account of impacts from a range of climate models to enable more robust long-term decision-making for water management. Flow changes assessed using fixed baseline and future time-slices differ from those using time-slices derived by model-based global temperature change from the pre-industrial period; the latter removes some uncertainty related to choice of emissions scenario and improves comparability between different climate models, but the preferred approach may depend on the application.

Marine data assimilation in the UK: the past, the present, and the vision for the future - Jozef Skákala; David Ford; Keith Haines; Amos Lawless; Matthew J. Martin; Philip Browne; Marcin Chrust; Stefano Ciavatta; Alison Fowler; Daniel Lea; Matthew Palmer; Andrea Rochner; et al. (Ocean Science, 2025)
In the last 2 decades, UK research institutes have led a wide range of developments in marine data assimilation (MDA), covering areas from operational applications in physics and biogeochemistry to fundamental theory. We highlight the emergence of strong collaboration in the UK MDA community over this period and the increasing unification of its tools. We focus on identifying the MDA stakeholder community and current/future areas of impact, as well as current trends and future opportunities. This includes the rapid growth of machine learning (ML)/artificial intelligence (AI) and digital-twin applications. We articulate a vision for the future, including the need for future types of observational data (whether planned missions or hypothetical) and how the community should respond to increases in computational power and new computer architectures (e.g. exascale computing). We contrast the requirements of different MDA areas, including physics, biogeochemistry, and coupled data assimilation (DA). Although the specifics of the vision depend on each area, common themes emerge. We advocate for balanced redistribution of new computational capability among increased model resolution, model complexity, more sophisticated DA algorithms, and uncertainty representation (e.g. ensembles). We also advocate for integrated approaches, such as strongly coupled DA (ocean–atmosphere, physics–biogeochemistry, and ocean–sea ice) and the use of ML/AI components (e.g. for multivariate increment balancing, bias correction, model emulation, observation re-gridding, or fusion).

Measuring Dietary Quality Among Toddlers in the Feeding Infants and Toddlers Study, 2016, Using the New Healthy Eating Index-Toddlers-2020 - Melissa C. Kay; Joel Hampton; Susan Pac; Lyndsey Huss; Alison L. Eldridge (Journal of the Academy of Nutrition and Dietetics, 2025)

Awareness and Support of Responsive Bottle Feeding Among WIC Counselors and Caregivers: A Formative Qualitative Study - Taylor N. Richardson; Alison K. Ventura; Ashley Brewer; Avan Shirwani; Belen de la Barrera; Melissa C. Kay (Journal of Nutrition Education and Behavior, 2024)

Beyond the local climate change uplift – The importance of changes in spatial structure on future fluvial flood risk in Great Britain - Paul Sayers; Adam Griffin; Jason Lowe; Dan Bernie; Sam Carr; Alison Kay; Lisa Stewart (Natural Hazards, 2024)
Widespread spatially coherent flood events can cause severe damage and disruption. Climate change has the potential to change the severity and frequency of such events. Despite this, assessment of future fluvial flood risk typically gives little to no consideration to potential changes in the spatial structure of future events. To understand the significance of this gap, climate model simulations are coupled with a national hydrological model to identify event spatially coherent present and future flood events. A statistical Empirical Copula is used to generate a large number of unseen events and linked to a national flood risk simulation model. The research finds that including changes in the spatial structure of flood events materially increases projected changes in risk when compared to conventional approaches based on local uplifts alone; increasing the projected change in Expected Annual Damage across Great Britain by a factor of ~ 1.5. The event-based approach is also shown to provide new insights into the extreme distribution fluvial risk including single event damage, damage seasons, and damage years. The results suggest the 1-in-100-year winter flood may increase from £1.3b to £2.1b, and the 1-in-100 year single event damage may rise from £1.1b today to £1.7b by the 2080s given a 4 °C rise in Global Mean Surface Temperature (assuming current adaptation policies continue and no population growth). Consequently, the findings suggest a much greater emphasis is needed on spatial ‘flood events’ if future risk is to be understood and adaptation responses appropriately framed. Graphical abstract

Determination and quantification of microbial communities and antimicrobial resistance on food through host DNA-depleted metagenomics - Samuel J. Bloomfield; Aldert L. Zomer; Justin O'Grady; Gemma L. Kay; John Wain; Nicol Janecko; Raphaëlle Palau; Alison E. Mather (Food Microbiology, 2023)

Combined effects of increased water temperature and cyanobacterial compounds exert heterogeneous effects on survival and ecological processes in key freshwater species - Oloyede A. Adekolurejo; Matthew Floyd; Alison M. Dunn; Paul Kay; Andrew P. Dean; Christopher Hassall (Oecologia, 2022)
Climate change is increasing water temperature and intensifying the incidence of cyanobacterial blooms worldwide. However, the combined effects of increased temperature and microcystin concentrations as co-stressors on survival and ecological processes in freshwater species are unclear. Here, using purified MC-LR and crude extract of toxigenic Microcystis aeruginosa , we tested the individual and combined effects of three water temperatures (15, 20, 25 °C) and a range of environmentally relevant concentrations of dissolved microcystin and crude extract (0.01–10 µg·L −1 ) on survival, growth inhibition, grazing and predation rates in three freshwater species: phytoplankton ( Scenedesmus quadricauda ), zooplankton ( Daphnia pulex ), and an invertebrate predator ( Ischnura elegans ). Purified MC-LR exerted a higher growth inhibitory effect on S. quadricauda compared to crude extract with the same concentration of MC-LR, while neither treatment affected its chlorophyll-a content or survival of D. pulex . Crude extract reduced grazing and survival of D. pulex and I. elegans , respectively. The combined effect of higher temperature and crude extract reduced I. elegans survival by 50% . Increased temperature reduced prey handing time in I. elegans by 49%, suggesting a higher predation rate. However, warming together with higher concentrations of crude extract jointly increased zooplankton grazing and reduced damselfly predation. Taken together, these results suggest crude extract, and not necessarily microcystin, can affect survival and productivity in freshwater species, although these effects may vary unevenly across trophic levels. Our findings highlight the importance of complex ecological mechanisms by which warming can exacerbate toxic effects of cyanobacterial bloom extracts on survival and functions among species in eutrophic freshwaters.

Adoptees’ views and experiences of direct-to-consumer (DTC) genomic testing: an exploratory interview study from the UK - Alison C. Kay; Nicola V. Taverner (Journal of Community Genetics, 2022)
Direct-to-consumer (DTC) genomic testing for ancestry and health may appeal to adoptees looking to fill gaps in their family information. There are only a handful of published studies on adoptees’ views and experiences of DTC testing and none of these is from the UK. The recent UK House of Commons Science and Technology Committee report (GB Parliament, House of Commons 2021) did not address the gains or challenges for adopted people specifically, although the Committee did consider that robust evidence of opportunities or risks for any user of a DTC testing kit is limited. In this study presented here, semi-structured interviews were conducted with ten UK adult adoptees recruited via social media. Reflexive thematic analysis (Braun and Clarke 2006, 2019) of the interview transcripts identified three main themes: Decisional influencers of longing, uncertainty and normalisation of DNA kit use; Informational drivers to gain clarity but avoid new worrisome information; and talk around Negotiating Visibility to birth family and commercial third parties. A further theme of Meaning Making related to adoptees’ views of testing outcomes as bringing feelings of resolution or discordance. This study identified many challenging deliberations for adoptees in evaluating whether to take a DTC test and what to do when their results were returned. Additionally, adoptees’ consideration of data privacy issues appears hampered by already having shared identifying information about themselves in their wider adoptee search. Further research is encouraged.

A globally relevant change taxonomy and evidence‐based change framework for land monitoring - Richard M. Lucas; Sophia German; Graciela Metternicht; Rebecca K. Schmidt; Christopher J. Owers; Suzanne M. Prober; Anna E. Richards; Sally Tetreault‐Campbell; Kristen J. Williams; Norman Mueller; Belle Tissott; Sean M. T. Chua; et al. (Global Change Biology, 2022)
A globally relevant and standardized taxonomy and framework for consistently describing land cover change based on evidence is presented, which makes use of structured land cover taxonomies and is underpinned by the Driver‐Pressure‐State‐Impact‐Response (DPSIR) framework. The Global Change Taxonomy currently lists 246 classes based on the notation ‘impact (pressure)’, with this encompassing the consequence of observed change and associated reason(s), and uses scale‐independent terms that factor in time. Evidence for different impacts is gathered through temporal comparison (e.g., days, decades apart) of land cover classes constructed and described from Environmental Descriptors (EDs; state indicators) with pre‐defined measurement units (e.g., m, %) or categories (e.g., species type). Evidence for pressures, whether abiotic, biotic or human‐influenced, is similarly accumulated, but EDs often differ from those used to determine impacts. Each impact and pressure term is defined separately, allowing flexible combination into ‘impact (pressure)’ categories, and all are listed in an openly accessible glossary to ensure consistent use and common understanding. The taxonomy and framework are globally relevant and can reference EDs quantified on the ground, retrieved/classified remotely (from ground‐based, airborne or spaceborne sensors) or predicted through modelling. By providing capacity to more consistently describe change processes—including land degradation, desertification and ecosystem restoration—the overall framework addresses a wide and diverse range of local to international needs including those relevant to policy, socioeconomics and land management. Actions in response to impacts and pressures and monitoring towards targets are also supported to assist future planning, including impact mitigation actions.

Differences in hydrological impacts using regional climate model and nested convection-permitting model data - Alison Kay (Climatic Change, 2022)
Assessing the potential impacts of climate change on river flows is critically important for adaptation. Data from global or nested regional climate models (GCMs/RCMs) are frequently used to drive hydrological models, but now there are also very high-resolution convection-permitting models (CPMs). Here, data from the first CPM climate ensemble for the UK, along with the RCM ensemble within which the CPM is nested, are used to drive a grid-based hydrological model. The performance for simulating baseline (1981–2000) river flows is compared between the RCM and the CPM, and the projections of future changes in seasonal mean flows and peak flows are compared across Britain (1981–2000 to 2061–2080). The baseline performance assessment shows that (before bias correction) the CPM generally performs better than the RCM, and bias correction of precipitation makes both the RCM and CPM perform more similarly to use of observation-based driving data. The analysis of future changes in flows shows that the CPM almost always gives higher flow changes than the RCM. If reliable, these differences in flow projections suggest that adaptation planning for high flows based on use of regional data may be insufficient, although planning for low flows may be slightly over-cautious. However, the availability of CPM data only for one RCM/GCM is a limitation for use in adaptation as it under-samples the uncertainty range. There are significant challenges to the wider application of CPM ensembles, including the high computational and data storage demands.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

How might climate change affect river flows across West Africa? - Ponnambalam Rameshwaran; Victoria A. Bell; Helen N. Davies; Alison L. Kay (Climatic Change, 2021)
West Africa and its semi-arid Sahelian region are one of the world’s most vulnerable regions to climate change with a history of extreme climate variability. There is still considerable uncertainty as to how projected climate change will affect precipitation at local and regional scales and the consequent impact on river flows and water resources across West Africa. Here, we aim to address this uncertainty by configuring a regional-scale hydrological model to West Africa. The model (hydrological modelling framework for West Africa—HMF-WA) simulates spatially consistent river flows on a 0.1° × 0.1° grid (approximately 10 km × 10 km) continuously across the whole domain and includes estimates of anthropogenic water use, wetland inundation, and local hydrological features such as endorheic regions. Regional-scale hydrological simulations driven by observed weather data are assessed against observed flows before undertaking an analysis of the impact of projected future climate scenarios from the CMIP5 on river flows up to the end of the twenty-first century. The results indicate that projected future changes in river flows are highly spatially variable across West Africa, particularly across the Sahelian region where the predicted changes are more pronounced. The study shows that median peak flows are projected to decrease by 23% in the west (e.g. Senegal) and increase by 80% in the eastern region (e.g. Chad) by the 2050s. The projected reductions in river flows in western Sahel lead to future droughts and water shortages more likely, while in the eastern Sahel, projected increases lead to future frequent floods.

National-scale analysis of future river flow and soil moisture droughts: potential changes in drought characteristics - Alison C. Rudd; A. L. Kay; V. A. Bell (Climatic Change, 2019)

Flood event attribution and damage estimation using national‐scale grid‐based modelling: Winter 2013/2014 in Great Britain - Alison L. Kay; Naomi Booth; Rob Lamb; Emma Raven; Nathalie Schaller; Sarah Sparrow (International Journal of Climatology, 2018)
A sequence of major flood events in Britain over the last two decades has prompted questions about the influence of anthropogenic greenhouse gas emissions on flood risk. Such questions are difficult to answer definitively, as a range of other factors are involved, but modelling techniques allow an assessment of how much the chance of occurrence of an event could have been altered by emissions. Here the floods of winter 2013/2014 in Great Britain are assessed by combining ensembles of climate model data with a national‐scale hydrological model and, for one severely impacted river basin (the Thames), a detailed analysis of flood inundation and the increased number of residential properties placed at risk. One climate model ensemble represents the range of possible weather under the current climate, while 11 alternative ensembles represent the weather as it could have been had past emissions not occurred. The pooled ensemble results show that emissions are likely to have increased the chance of occurrence of these floods across much of the country, with a stronger influence on longer duration peaks (~10 days or more) than for shorter durations (consistent with observations). However, there is substantial variation in results between alternative ensembles, with some suggesting likely decreases in the chance of flood occurrence, at least in some regions of the country. The influence on flows and property flooding varies spatially, due to both spatial variation in the influence on precipitation and variation in physical properties that affect the transformation of precipitation to river flow and flood impacts, including flood defences. This complexity highlights the importance of using hydrological modelling to attribute hydrological impacts from meteorological changes. Changes in snow occurrence in a warming climate are also shown to be important, with effects varying spatially.

Developing Marine Protected Area Networks in the Coral Triangle: Good Practices for Expanding the Coral Triangle Marine Protected Area System - Rebecca Weeks; Porfirio M. Aliño; Scott Atkinson; Pacifico Beldia; Augustine Binson; Wilfredo L. Campos; Rili Djohani; Alison L. Green; Richard Hamilton; Vera Horigue; Robecca Jumin; Kay Kalim; et al. (Coastal Management, 2014)

The social, economic, and environmental contributions of Pan African Sanctuary Alliance primate sanctuaries in Africa - Gina M. Ferrie; Kay H. Farmer; Chris W. Kuhar; Alison P. Grand; Julie Sherman; Tammie L. Bettinger (Biodiversity and Conservation, 2014)

Climate change and river flooding: part 1 classifying the sensitivity of British catchments - Christel Prudhomme; Sue Crooks; Alison L. Kay; Nick Reynard (Climatic Change, 2013)

Climate change and river flooding: Part 2 sensitivity characterisation for british catchments and example vulnerability assessments - Christel Prudhomme; Alison L. Kay; Sue Crooks; Nick Reynard (Climatic Change, 2013)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Prediagnostic concentrations of plasma genistein and prostate cancer risk in 1,605 men with prostate cancer and 1,697 matched control participants in EPIC - Ruth C. Travis; Naomi E. Allen; Paul N. Appleby; Alison Price; Rudolf Kaaks; Jenny Chang-Claude; Heiner Boeing; Krasimira Aleksandrova; Anne Tjønneland; Nina Føns Johnsen; Kim Overvad; J. Ramón Quirós; et al. (Cancer Causes & Control, 2012)

Erratum to: Meat, poultry and fish and risk of colorectal cancer: pooled analysis of data from the UK dietary cohort consortium - Elizabeth A. Spencer; Timothy J. Key; Paul N. Appleby; Christina C. Dahm; Ruth H. Keogh; Ian S. Fentiman; Tasnime Akbaraly; Eric J. Brunner; Victoria Burley; Janet E. Cade; Darren C. Greenwood; Alison M. Stephen; et al. (Cancer Causes & Control, 2011)

Meat, poultry and fish and risk of colorectal cancer: pooled analysis of data from the UK dietary cohort consortium - Elizabeth A. Spencer; Timothy J. Key; Paul N. Appleby; Christina C. Dahm; Ruth H. Keogh; Ian S. Fentiman; Tasnime Akbaraly; Eric J. Brunner; Victoria Burley; Janet E. Cade; Darren C. Greenwood; Alison M. Stephen; et al. (Cancer Causes & Control, 2010)

Influence Diagrams for Representing Uncertainty in Climate-Related Propositions - Jim Hall; Craig Twyman; Alison Kay (Climatic Change, 2005)

The relationship between the rate of starch synthesis, the adenosine 5′-diphosphoglucose concentration and the amylose content of starch in developing pea embryos - Belinda R. Clarke; Kay Denyer; Colin F. Jenner; Alison M. Smith (Planta, 1999)